Analisis Dampak Dan Kesiapsiagaan Dalam Penanggulangan Bencana Tsunami Serta Program Psikososial Bagi Korban: Studi Literatur - Sembiring, Zamalludin; Irdyna, Razita; Khanis Natun Zakhziah, Khalila; Flora, Citra; Bianda Putri, Nayla; Septi Ramadani, Suci; Syahrani, Revana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the impacts of tsunami disasters, examine preparedness strategies in disaster management, and describe psychosocial programs for victims. The research employs a descriptive qualitative approach through a literature review by analyzing various scientific sources such as journals, books, and disaster reports. The results indicate that tsunamis have multidimensional impacts, including infrastructure damage, economic losses, and psychological disturbances. Disaster management efforts need to be carried out in an integrated manner through structural and non-structural mitigation, such as infrastructure development, strengthening early warning systems, and conducting disaster education and simulations. In addition, trauma healing programs play an important role in restoring the psychological condition of victims, both children and adults. The integration of preparedness, mitigation, and psychosocial recovery is expected to minimize the impacts of tsunami disasters more effectively.